The effect of value creation and reputation on the intangible success of born global new internet ventures / Shamsul Baharin Saihani - Saihani, Shamsul Baharin (2018)
Many researchers, academics and practitioners were captured by surprise when a growing number of new internet ventures in the early twenty-first century successfully internationalizing their businesses. Undoubtedly, these new internet ventures and which is also sometimes called as born global signify an entirely novel type of firms by disregarding the established views of firm internationalization and creating a paradigm shift to the international business landscapes. This study looks into the significance of value creation business-to-consumer model in e-commerce and together with corporate reputation constructs in influencing the intangible success of born global new internet ventures from the business owners or managers’ perspectives. In addition, this study would help to explain the moderating effect of environmental dynamism. The outcomes of this study are able to assist other new internet ventures particularly among micro and small size companies, financial and academic institutions, as well as policy makers in devising successful internationalization strategies for new internet ventures. Understanding the outcomes of this study is also crucial to the future business owners or managers so that they can avoid costly mistakes to successfully internationalize via export. Using resource-based view (RBV) and international performance model i.e. export performance, a framework was deduced. The study draws on a study of exploratory nature using quantitative method. Non-probability sampling using purposive method was used. The questionnaire was distributed to 600 micro companies conducting e-commerce in Malaysia identified from Lelong directory, SME Bank online directory and Persatuan Usahawan Internet Malaysia directory. Using a final sample size of 184, thus yielding 33.8% return rate was used in the study. This study used Partial Least Square-Structured Equation Modeling (PLS-SEM) analysis. The findings indicate five out of the twelve constructs are positively significant to the intangible success of born global new internet ventures such as value creation of efficiency, capability reputation, responsibility reputation, and including two moderating relationships on environmental dynamism (e.g. value creation of efficiency and responsibility reputation).